2004
DOI: 10.1111/j.1467-9620.2004.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Mentor-Novice Conversations about Teaching: A Comparison of Two U.S. and Two Chinese Cases

Abstract: Mentor-novice collaborative reflection about teaching is crucial to the development of novices’ professional knowledge. However, few studies examine content and forms of mentor-novice conversations and opportunities that such interactions create for developing professional knowledge. Drawing on observation data from two U.S. and two Chinese mentor-novice pairs in induction contexts, this study analyzed the content and forms of mentor-novice conversations about novices’ lessons. We found that the U.S. and Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 33 publications
0
47
1
4
Order By: Relevance
“…A critical component of approximation is mentors' feedback, or the reviews of performances. Historically, U.S. mentors have provided praise for novices and withheld critical feedback because it is thought that positive feedback will nurture novice development (Wang et al, 2004). In this case, John engaged in discerning feedback that included both praise and critique.…”
Section: Approximations Of Practicementioning
confidence: 97%
See 3 more Smart Citations
“…A critical component of approximation is mentors' feedback, or the reviews of performances. Historically, U.S. mentors have provided praise for novices and withheld critical feedback because it is thought that positive feedback will nurture novice development (Wang et al, 2004). In this case, John engaged in discerning feedback that included both praise and critique.…”
Section: Approximations Of Practicementioning
confidence: 97%
“…We identified all possible configurations. This approach to looking at relationships among topics (e.g., subject, students, teaching) was seen in previous research on mentoring exchanges (Wang et al, 2004). Fourth, we conducted comparisons between mentoreteacher pairs for topics and multiple-code frequencies and configurations.…”
Section: Data Collection and Analysismentioning
confidence: 98%
See 2 more Smart Citations
“…This leads to providing different learning and mentoring experiences for teacher candidates in teacher education programs, which in turn shape teacher professional development and consequently student learning. For example, where teaching is conceptualized variously across cultures, case study research has shown that mentoring of teacher candidates has different impacts on teacher learning (Feiman-Nemser & Parker, 1992;Wang, 2001;Wang, Strong, & Odell, 2004). Further exploration is merited of the kinds of teaching practice and mentoring we want to connect to teacher learning and how to connect it.…”
Section: What We Hearmentioning
confidence: 99%